(untitled) (Baghdad Science Journal, 2024)
The ultrafunctional potential of zinc oxide (ZnO) and copper oxide (CuO) nanoparticles (NPs) has generated a great interest in using such metal oxides as remarkable and electroactive nanocomposites in the studies on potentiometry and sensors. These nano-oxides were prepared from the extract of Leucaena leucocephala seeds as an environmentally friendly process. The development of a ZnO/CuO “core-shell nanocomposite-modified” coated copper wire film sensor was proposed as a new method for potentiometric determination of pseudoephedrine hydrochloride (PSD) in pure and pharmaceutical dosage forms. With the existence of polyvinyl chloride (PVC) as a polymer with high molecular weight and “o-nitrophenyl octyl ether (o-NPOE) as a solvent mediator”, PSD was combined with phosphotungstic acid (PTA) to produce pseudoephedrine hydrochloride-phosphotungstate (PSD-PT) as a sensing substance. The improved sensor showed a very high sensitivity and selectivity for determining and quantifying the PSD with a linear relationship of 1.0×10-8-1.0×10-2 mol L-1. It was estimated that the regression equation was represented by the EmV = (-58.143) log [PSD] + 526.71. With the proposed sensors, pseudoephedrine hydrochloride could be effectively determined in pure and commercial product forms.